Pengaruh Sumber Daya Manusia Terhadap Kemampuan Kerja Pegawai - Herma Yunita; Septi Tri Utami; Ayu Megawati (Forum Kerjasama Pendidikan Tinggi, 2022)
The purpose of this study was to see the effect and analyze the influence of human resource competence on the work of Bappeda office employees in Lubuklinggau City. The respondents in this study were employees of the Lubuklinggau City Bappeda office as many as 35 respondents, the sample was selected by purposive sampling. The results of the study show that there is an influence of human resource competence on employee work which can be seen t count (6.701) > t table (2.080). The strong relationship between human resource competence and employee work is reflected in the R value of 0.825 which indicates that there is a strong relationship between human resource competence and employee work. Furthermore, the magnitude of the influence of human resource competence is 68.1% on employee work and the remaining 31.9% is influenced by other factors.